Diversifikasi produk pangan berbasis sumber daya lokal jantung pisang kepok (Musa paradisiaca) melalui karakteristik fisikokimia - Jacky Anggara Nenohai; Ima Rosyida; Nur Indah Agustina; Yudhi Utomo; Sumari Sumari (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
The banana plant that is still underutilized compared to the fruit part is the heart of the banana. Even though the heart of the banana has many benefits and nutritional content that is good for health. Seeing the potential of the heart of the banana can improve public health, so food diversification efforts such as flour and substitutes for the basic ingredients of food to produce new forms of product innovation, so research was carried out to test its content, which aims to inform the public that the heart of the banana can be beneficial for health in processing into flour. This research was carried out in March-April 2022 at the Chemistry Education Laboratory of Nusa Cendana University, Kupang. There are four stages in this study, including 1) Manufacture of the heart of banana flour; 2) Proximate Test of the heart of banana flour; 3) Diversification of products based on the heart of banana flour, 4) Organoleptic test of products based on the heart of banana flour on 52 panelists. The results of research on the manufacture of banana heart flour are substituents of flour that have good nutritional content with relatively good character if used as a substitute for wheat flour because many parameters meet the quality requirements of wheat flour, namely the physical characteristics of banana heart flour meet the test requirements for shape. In contrast, the aroma, color, and taste in accordance with the characteristics of the nutritional content meet the moisture content proteins, fats, and carbohydrates. In contrast, the ash content does not complete because the mineral content in each ingredient is different and the manufacture of wheat flour. The result of the diversification of the products made, namely the Genital Widow Cake / Monde chips made from banana heart flour, are also included in the excellent category where the aroma, taste, and acceptance of the product are accepted in the community.